Team Knowledge and Coordination in Geographically Distributed Software Development - Espinosa, J. Alberto; Slaughter, Sandra A.; Kraut, Robert E.; Herbsleb, James D. (Journal of Management Information Systems, 2007)
Coordinating software tasks across geographic locations is difficult because of factors like: limited opportunities for interaction, lack of contextual references, and leaner communication media. Team cognition research suggests that team knowledge helps members coordinate because they can anticipate task issues more accurately, communicate more efficiently and find expertise within the team, among other things. In this field study we investigate one large team of geographically distributed developers collaborating on a software task in a telecommunications firm to better understand how team knowledge influences coordination effectiveness and how this varies with geographic dispersion. Our findings reveal that: software developers have different types of coordination needs; coordination across sites is more challenging than within a site; team knowledge helps members coordinate, but more so when they are separated by geographic distance; and the effect of different types of team knowledge on coordination effectiveness differs between co-located and geographically dispersed collaborators.